A Deming Cycle as a Tool of Improving A Continuous Service Quality - M. Nur Nasution (Indonesian Management and Accounting Research, 2006)
Every industry or organization must commit to make a change or improvement due to the pressure from the internal and external environment. If not, the existence of its industry will be threatened to collapse. There are six steps in improving a quality of dynamic management. A Deming cycle is a model for continuing improvement comprising four main components that are planning, doing, checking or studying and acting. In planning, the improvement is based on the strategic planning. Doing it is based on the change of management, and the choking is based on the culture of organization, and the acting is based on the qualified leader. It is acknowledged that all methods and work process improvement will provide a variety of benefits or outcomes namely; quality improvement, low costs, high productivity, low price, high market shares, guarantee of survival industry, a wide work field in cremate and work satisfaction.Key words: A Deming cycle, continuous improvement and dynamic quality management, service quality Improvement strategy, and a customer's satisfaction strategy.